Voces indígenas de Tagual La Pó como referencial de una política pública de protección de territorios - Vásquez Santamaría, Jorge Eduardo (Universidad de San Buenaventura - Cali, 2017)
The rescuing of indigenous voices in their native tongues and in their hometowns, was traced as the means to respect and value ancestral thoughts as a fundamental principle of land symbolization, object of protection from indigenous voices of the shelter Tagual La Pó, gave form to the original decisional flow which nurtures the construction of the referential of a public policy in the department of Antioquia. Indigenous voices were rescued from the oral historical instruments which questioned the representations and interpretations of the land, the relations with it, and the defined territorial realities such as public issues which currently victimize the members of the Tagual La Pó shelter, identifying a distance with the experience of indigenous communities of the sub regions of Urabá and the southeast of Antioquia.